ACTORS’ COMMUNICATION STRATEGY IN ENFORCING ISLAMIC SHARI’A IN NORTH ACEH, INDONESIA - Maryam; Endang Larasati Setianingsih; Kismartini; Ida Hayu Dwimawanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
There are ups and downs, obstacles, challenges, and problems during the implementation and enforcement of Islamic sharia in North Aceh. The legal basis for enforcing Islamic sharia in Aceh is based on Qanun Number 5 of 2000 concerning the Implementation of Islamic Sharia as the foundation for the implementation of Islamic law. The supervision and control of the Qanun implementation belong to the Wilayatul Hisbah (Shari'a Police) as the authorized and legal agency. This study aims to analyze the actors’ communication strategy in enforcing Islamic shari’a in North Aceh, Indonesia. This study used a qualitative descriptive analysis. Observation, interviews, documentation were used to collect data. This study revealed that there was a fluctuation in the number of violations during the implementation of Islamic law in North Aceh. As its communication strategy, Wilayatul Hisbah of North Aceh conducted the following programs: (1) Enhancing understanding towards Islamic values; (2) Enhancing understanding and practice of the Koran; (3) Enhancing the quality of religious life and tolerance; (4) Fostering da’wah and Islamic sharia; (5) Deepening, developing and fostering sharia; and (6) Strengthening, developing, empowering and enhancing Islamic Sharia Court Cooperation. These six programs required immense and intense communication strategy. However, not all these programs have been implemented optimally due to factors such as a lack of budget, human resources, and the reluctance of actors. Such phenomenon occurred because of weak communication among actors resulting in the occurrence of many obstacles during the programs implementation.